The Effect of Human Resource Planning Policy Implementation in Transforming Human Resources Performance of PT Indowebhost Kreasi - Hashim Azwar Sulaiman (Journal Boas : Business, Economics, Accounting And Management, 2022)
Preparation is one of the key things to do to avoid failures, one of the examples are human resource planning concept. Human resources performance at PT IWK are still not on the maximum level, thus creating a problem at the beginning of the company formation. Performance transformation at PT IWK could be done by the help of the policy implementation of human resources planning. Based on the background, purpose of this paper are to understand the effects of human resources planning policy on transforming human resources performances at PT IndoWebhost Kreasi. While the formulation of the problem on this paper are how the effects of human resources planning policy on transforming human resources performances at PT IndoWebhost Kreasi. PT IWK is a company that provides internet, data and managed services communication for plantations companies and other industries in Medan. This paper uses a qualitative approach to with the type of descriptive research Primary data collection techniques through in-depth interview and documentation. Retrieval of secondary data by obtaining documents provided by the company. The analysis of the data is done by reducing the data, presenting the data and finished by drawing conclusions. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the company. This paper uses a qualitative approach to with the type of descriptive research Primary data collection techniques through in-depth interview and documentation. Retrieval of secondary data by obtaining documents provided by the company. The analysis of the data is done by reducing the data, presenting the data and finished by drawing conclusions. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the company. This paper uses a qualitative approach to with the type of descriptive research Primary data collection techniques through in-depth interview and documentation. Retrieval of secondary data by obtaining documents provided by the company. The analysis of the data is done by reducing the data, presenting the data and finished by drawing conclusions. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the company. Retrieval of secondary data by obtaining documents provided by the company. The analysis of the data is done by reducing the data, presenting the data and finished by drawing conclusions. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the company. Retrieval of secondary data by obtaining documents provided by the company. The analysis of the data is done by reducing the data, presenting the data and finished by drawing conclusions. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the company. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the company. The results of this paper are human resources planning policy implementation are doing good based on the transformation on human resources performances. But, there is still a need for improvement on the communication process of the implementation, in by doing so could create a better planning and resulting in the effectiveness level that is set by the compan